Embodied creativity : searching for the dancing-self - Spohr, Karolin (2020)
Based on the inquiries into the genealogies of creativity as a concept in both Western and Eastern traditions, and tracing the literature around creativity as an object of research in Creativity Studies, this dissertation tries to situate creativity within the realm of dance improvisation and looks at how the application and understanding of creativity are closely connected to the cultural factors surrounding them. Acknowledging creativity as a universal and culturally related phenomenon which can be accessed by individuals through both conscious practices and open-mindedness, and seeing dance performance as a manifestation of creativity, this research asks, first, what is creativity in performing practice and, second, is there a dancing-self in the performer. It will apply the study of creativity onto the personal level and into the context of dance. To answer these corresponding research questions, this study will be divided into two parts. The first part is a theoretical study of the literature of creativity from traditional Western and Eastern viewpoints of the creative person to recent cultural and psychological research approaches about creativity in performance. The second part is a practical study aligned with the results deduced from the theoretical overview in the first part. It is a Case Study of three professional dancers of Contemporary Dance working at the State Theatre in Bremen. Through studying the recordings of their improvised movements with them, using the methods of video-stimulated-recall and semi-open interviews, a qualitative study will be conducted to understand how creativity emerges with relevance to the theoretical findings as well as the idea of the dancing-self.